Expression of Epstein-Barr virus (EBV) transcripts encoding homologues to important human proteins in diverse EBV associated diseases. Issue 2 (1st April 1999) - Hayes, D P; Brink, A A; Vervoort, M B; Middeldorp, J M; Meijer, C J; van den Brule, A J
Abstract : AIMS: To examine the expression of Epstein-Barr virus (EBV) transcripts encoding proteins homologous to important human proteins in diverse EBV associated diseases. The proteins were: BHRF1 (homologous to Bcl-2), BDLF2 (homologous to cyclin B1), BARF1 (homologous to intercellular cell adhesion molecule 1 (ICAM-1)), and BCRF1 (viral IL-10 (vIL-10), homologous to human IL-10 (hIL-10)). METHODS: Six cases of oral hairy leukoplakia, seven of Hodgkin's disease, eight of T cell non-Hodgkin's lymphoma, and nine of nasopharyngeal carcinoma were examined at the mRNA level using either the reverse transcriptase polymerase chain reaction (RT-PCR) or nucleic acid sequence based amplification (NASBA). Different primer sets allowed the differentiation by RT-PCR of the latent (Cp/Wp driven) and lytic (Hp driven) transcripts of BHRF1. A specific NASBA reaction was developed for the detection of vIL-10 and BDLF2 transcripts and this was tested initially on cell lines and later on clinical samples. RESULTS: vIL-10 and BDLF2 were expressed almost exclusively in oral hairy leukoplakia, whereas BARF1 transcripts were present in all cases of nasopharyngeal carcinoma, with weak expression in one oral hairy leukoplakia and isolated cases of lymphoid malignancy. Both BHRF1 transcripts were detected across the range of tissues tested, but strong expression of lytic BHRF1 transcripts was seen only in oral hairy leukoplakia. CONCLUSIONS: vIL-10 and BDLF2 transcripts are expressed during productive EBV infection and are unlikely to be important in the pathogenesis of EBV associated malignancies. BARF1 appears to be expressed preferentially during viral latency and is more closely associated with malignant rather than benign epithelial proliferations. The alternative transcripts derived from the BHRF1 open reading frame may have very different roles during latent or productive infection.